APLIKASI GEOBOARD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA - Lucyana, Bella Mei Gita; Handayani, Aprilia Dwi; Mudjion, Mohammad (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2025)
This classroom action research was conducted in two cycles in the fourth grade of SDN Burengan 3 Kediri City, consisting of 27 students. This research was motivated by the low learning outcomes of students in Mathematics, particularly on the material about area of squares and rectangles, with a class average score of 50.37 that required improvement. The main objective of this research was to describe the improvement in learning outcomes of fourth-grade students at SDN Burengan 3 Kediri City on this material through the use of geoboard media. This research used the Kemmis & McTaggart Classroom Action Research (CAR) design, which includes the stages of planning, implementation, observation, and reflection carried out repeatedly in each cycle. The results showed an increase in student learning outcomes in each cycle. In the pre-cycle stage, the average student learning outcome was 50.37%. After implementing geoboard media in Cycle I, student learning mastery increased to 51.58% and was categorized as fairly good. A significant improvement occurred in Cycle II, with the percentage of learning mastery reaching 92.52%, which was included in the good category, and the class average score increased to 89.63. Based on these results, it can be concluded that the use of geoboard media proved effective in improving the learning outcomes of fourth-grade students at SDN Burengan 3 Kediri City on the material about area of squares and rectangles. ABSTRAKPenelitian tindakan kelas ini dilaksanakan dalam dua siklus di kelas IV SDN Burengan 3 Kota Kediri yang terdiri dari 27 siswa. Penelitian ini dilatarbelakangi oleh rendahnya hasil belajar siswa pada mata pelajaran Matematika, khususnya materi luas persegi dan persegi panjang, dengan nilai rata-rata kelas sebesar 50,37 yang memerlukan perbaikan. Tujuan utama penelitian ini adalah untuk mendeskripsikan peningkatan hasil belajar siswa kelas IV SDN Burengan 3 Kota Kediri pada materi tersebut melalui penggunaan media geoboard. Penelitian ini menggunakan desain Penelitian Tindakan Kelas (PTK) model Kemmis & Mc. Taggart yang meliputi tahap perencanaan, pelaksanaan, pengamatan, dan refleksi yang dilakukan secara berulang dalam setiap siklus. Hasil penelitian menunjukkan adanya peningkatan hasil belajar siswa pada setiap siklus. Pada tahap pra-siklus, rata-rata hasil belajar siswa adalah 50,37%. Setelah implementasi media geoboard pada Siklus I, ketuntasan belajar siswa meningkat menjadi 51,58% dan dikategorikan cukup baik. Peningkatan signifikan terjadi pada Siklus II, dengan persentase ketuntasan belajar mencapai 92,52% yang termasuk dalam kategori baik, serta nilai rata-rata kelas meningkat menjadi 89,63. Berdasarkan hasil tersebut, dapat disimpulkan bahwa penggunaan media geoboard terbukti efektif dalam meningkatkan hasil belajar siswa kelas IV SDN Burengan 3 Kota Kediri pada materi luas persegi dan persegi panjang.